"Secrets of the Interconnections in the Holy Qur'an: New Interpretation of the so Called "Disconnected Letters - Al-Rawajfa, Ayman Eid (Journal of Humanities & Social Sciences, 2019)
Proceeding from the thoroughly revealed and elucidated Holy Quran, the paper addresses the disconnected letters and their signified interpretations. The research methodology employed relies on the interpretation of the Qur’an by the Qur’an as stated in Surah Al-An'am (6), verse No. 38: “We have neglected nothing in the Book, then unto their Lord they (all) shall be gathered”. Two intertwined thoughts are examined in this paper. First, disconnected letters can be compared to the list of symbols, which are recurrently used in books and scientific research; for example, the speed of light has a constant symbol that researchers of different language backgrounds can know. Second, the theory of set point net is used to demystify the secrets of interconnections between two Surahs, two verses or two letters in the Holy Qur’an. The paper finally finds that the letters are disconnected but strongly interconnected.
Keywords: cut letters; scientific symbols; the interdependence of the Qur'an; Symmetry network theory